A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Analyses of Different Approaches for Virtual Towing Tank Uncertainty Assessment - Simone Bozzo; Diego Villa; Simone Mancini (Journal of Marine Science and Engineering, 2025)
The assessment for the resistance of a new ship under design can be performed through the Experimental Fluid Dynamics (EFD) or the Computational Fluid Dynamics (CFD) approach; both have their own Uncertainty Assessment (UA). In CFD field, the Verification and Validation (V&V) procedures take into account the approximations for numerical issues and the assumptions adopted to describe the physical phenomena to assess UA. Different theoretical approaches have become available over time; nevertheless, a single comprehensive solution to achieve the UA remains still unknown because as the theoretical methodology varies, the outcome changes. In current work, four different literature approaches will be augmented to perform a V&V analysis for two kinds of model hulls, tested at different speeds and compared with the experimental data. The investigations performed among results lead to the division of all the approaches into the three and four solutions families and to define a robust procedure to identify a reasonable value for the numerical uncertainty assessment. Regarding the robustness and the UA of the approaches, the first family proved successful in only 55% of cases with a UA mean value below 2.01%, while the second one always provides a quantification but with a mean value of 6.65%.